Implementasi Wakaf Produktif Masjid Roudhotul Muchlisin Jember Perspektif KHI dan UU No. 41 Tahun 2004 - Ridho Syahbibi; Muhammad Faisol (Rechtenstudent, 2020)
The implementation of productive waqf for the Roudhotul Muchlisin Mosque, Kaliwates District, Jember Regency is a very important thing to do, because the mosque, which was built on this waqf land, is now a new religious tourism icon in Jember Regency. With typical Middle Eastern architecture and in recent years, it has experienced significant developments in the physical construction of mosques, public facilities, and a food corner. This research uses a qualitative approach with descriptive research type. The research data were collected using three techniques, namely: observation, in-depth interviews, and documentation. The management of the mosque's waqf uses the idarah system which means governance in regulating and managing the mosque. As for what is regulated in the Idarah system, among others: management, finance, and administration or secretarial. The implementation of productive waqf for the Roudhotul Muchlisin Mosque is following the Compilation of Islamic Law and Law Number 41 of 2004 concerning Waqf. Because it has developed TPQ Education, the establishment and development of a food corner to empower the economy of the people. The takmir of the Roudhotul Muchlisin Mosque, Kaliwates Subdistrict, Jember Regency, also plans to build a health clinic that aims to make the congregation's and the surrounding community's access to health easier and more beneficial for the people.